Unpacking healthy workplace practices effects on intrinsic motivation of ICT professionals: A SEM approach - Rasheed Olawale Azeez; Tinuke Moradeke Fapohunda; Foluso Ilesanmi Jayeoba (Trends Economics and Management, 2019)
Purpose of the article: This study investigated the effects of healthy workplace practices through its dimensions (work-life balance, growth and development, employee recognition, employee involvement, and health and safety) on intrinsic motivation of ICT professionals working in the Nigerian public sector. Methodology/methods: The study employed the survey research design, and the simple random sampling technique was used to administer 315 copies of questionnaires distributed to ICT professionals working with the Lagos State Government, Nigeria. Scientific aim: Based on the existing literature, five hypotheses were tested using the inferential statistical technique of a co-variance based structural equation modelling of the Analysis of Moment Structure (AMOS) version 21. The outcomes of the multivariate statistical procedures yielded good fit indexes from the confirmatory factor analysis, measurement and structural models, respectively. Findings: The results of the tested hypotheses signposted a significant effect of work-life balance, growth and development, involvement, and employees' health and safety on intrinsic motivation. Also, an insignificant effect of employees' recognition was established on intrinsic motivation. Conclusions: This study concludes that employers in the public sector (government) should endeavour to restructure their workplace policies and practices to become healthy in nature with a view to enhancing employees' intrinsic motivation and well-being on the one hand and, viability and efficaciousness of the public sector on the other.
Keywords: M12; H70; 650; work-life balance; growth and development; involvement; recognition; health and safety; intrinsic motivation